Remanufacturing Process Planning Considering Quality Uncertainties, Environmental Taxes and Incentives - (:unkn) unknown (My University, 2020)
As environmental issues are gradually being valued by governments and societies, companies have begun to engage in economic sustainable practices such as remanufacturing, reuse and recycling, among other socially responsible practices. The broader impact of these practices enables companies to archive the goal of circular economies. Under normal circumstances, consumers’ used products have often been released into landfills, resulting in environmental pollution. This is especially so for electronic products since most materials used in their production are non-biodegradable. This research addresses the practice of remanufacturing. The remanufacturing value of the products gradually declines with the usage--also referred to as the product resident time. So the remanufacturer must decide when to acquire these end of life products from customers, to carry out remanufacturing at maximum benefits. Companies face logistical challenges in the remanufacturing process, including uncertainties in the quality and quantity of returned products, and uncertainties in the process variables including process times and resource availability. In order to maximize expected profits, we provide a decision model for finding the optimal quality threshold to accept into the system and also show the variability in the profit percentages when products are returned at various stages in their life cycle. The model also considers a system that not only remanufactures products but also salvages components and uses them in the remanufacturing process. The model also allows for purchases of new components from suppliers as needed. The model also includes environmental factors such as emissions taxes and remanufacturing government incentives. The model is applied to a case study of a real control drive remanufacturing process, with two types of products that have interchangeable key components. The results confirm that the quality threshold is indeed of significance in the process. The demand forecast for remanufactured products in the secondary market is even more significant, driving the acceptable threshold quality to as low as 0.25 on a scale of 0 (worst quality) to 1 (best quality). Lastly, the results show that the resident time (time of return after the product was first sold in the first market) also significantly impacts the profit.
Keywords: Environmental taxes; Quality uncertainties; Remanufacturing planning